Ответ:
[tex]x_1=-2, \ x_2=2, \ x_3=3[/tex]
Пошаговое объяснение:
[tex](2x^{4}-34)(3-x)=2(x-3)\\(2x^{4}-34)(3-x)-2(x-3)=0\\(2x^{4}-34)(-(x-3))-2(x-3)=0\\(x-3)(-(2x^{4}-34)-2)=0\\(x-3)(-2x^{4}+34-2)=0\\(x-3)(-2x^{4}+32)=0\\x-3=0 \ \ \ -2x^{4}+32=0\\x=3 \ \ \ \ \ \ \ \ -2x^{4}=-32\\|\ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ x^{4}=16\\|\ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ x=\pm 2\\x_1=-2, \ x_2=2, \ x_3=3[/tex]
Copyright © 2025 SCHOLAR.TIPS - All rights reserved.
Answers & Comments
Verified answer
Ответ:
[tex]x_1=-2, \ x_2=2, \ x_3=3[/tex]
Пошаговое объяснение:
[tex](2x^{4}-34)(3-x)=2(x-3)\\(2x^{4}-34)(3-x)-2(x-3)=0\\(2x^{4}-34)(-(x-3))-2(x-3)=0\\(x-3)(-(2x^{4}-34)-2)=0\\(x-3)(-2x^{4}+34-2)=0\\(x-3)(-2x^{4}+32)=0\\x-3=0 \ \ \ -2x^{4}+32=0\\x=3 \ \ \ \ \ \ \ \ -2x^{4}=-32\\|\ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ x^{4}=16\\|\ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ x=\pm 2\\x_1=-2, \ x_2=2, \ x_3=3[/tex]